How did ancient human activities influence the properties and development of soil?—a case study of the Yangshao Village cultural relic site, Henan Province - Zha, Lisi; Wang, Wenjing; Zhong, Junhong; Su, Yiqi; Chang, Dandan (Frontiers in Environmental Science, 2024)
What were the effects of paleoanthropogenic activities on the physicochemical properties and degree of development of soil? To search this answer, we can not only understand the different types of ancient human activities, but also explore the intensity and characteristics of the activities. In this study, soil samples from different soil layers and two profiles in Yangshao Village cultural site in Henan Province were collected. They were analyzed and compared so that we found the paleoanthropogenic activities started in the relatively low-lying area, in which the slash-and-burn activities resulted in the soil filled with intrusions such as charcoal debris and ceramic shards. At the same time, the coarsegrained matter was affected by the plowing activities and mostly decomposed into fine particles, and the content of clay particles reached an extreme value. The total nitrogen, phosphorus and calcium carbonate content exceeded the average value of natural profile, indicating that the ancient humans had used human and animal feces to a certain extent to restore the fertility of arable land. Overall, the ancient human activities basically hindered the development of the soil, especially the ground created due to habitation activities. From the type and content of clay minerals, it could be seen that the soil in this layer has been transported from other places, with a high content of clay particles, and had experienced fire baking, and it was assumed that the ground was used to cover the grain or bury the garbage and laid with the clay in order to achieve the effect of sealing. As a result, the soil voids and structure had been damaged to some extent, which prevented the downward leaching or precipitation of soil particles and minerals to a certain extent, thus affecting soil development.